Genome-wide identification, characterization, and functional analysis of lncRNAs in Hevea brasiliensis - Wang, Lingling; Wang, Jingyi; Chen, Hui; Hu, Bin (Frontiers in Plant Science, 2022)
Natural rubber (NR) is an essential industrial raw material widely used in our life. Hevea brasiliensis (Reyan7-33-97) is an economic plant producing natural rubber. Long non-coding RNAs (lncRNAs) are emerging as crucial regulators in numerous biological processes while the characterization and analysis of lncRNAs in Hevea brasiliensis are still largely unrevealed. We integrated the transcriptome datasets from multiple tissues to identify rubber lncRNAs. As a result, 12,029 lncRNAs were found and characterized with notably distinctive features such as longer exon, lower expression levels and GC content, and more tissue specificity in comparison with mRNAs. We discovered thousands of tissue-specific lncRNAs in rubber root, latex, bark, leaf, flower, and seed tissues. The functional enrichment result reveals that tissue-specific lncRNAs are potentially referred to particular functions of tissues, while the non-tissue specific is related to the translation and metabolic processes. In the present study, a comprehensive lncRNA dataset was identified and its functional profile in Hevea brasiliensis was explored, which provides an annotation resource and important clues to understand the biological functions of lncRNAs in Hevea brasiliensis.